Natural Killer Cell Mediated Antibody-Dependent Cellular Cytotoxicity in Tumor Immunotherapy with Therapeutic Antibodies - Seidel, Ursula J.; Schlegel, Patrick; Lang, Peter (Frontiers in Immunology, 2013)
In the last decade several therapeutic antibodies have been FDA and EMEA approved. Although their mechanisms of action in vivo is not fully elucidated, antibody-dependent cellular cytotoxicity (ADCC) mediated by natural killer (NK) cells is presumed to be a key effector function. A substantial role of ADCC has been demonstrated in vitro and in mouse tumour models. However, a direct in vivo effect of ADCC in tumour reactivity in humans remains to be shown. Several studies revealed a predictive value of FcγRIIIa-V158F polymorphism in monoclonal antibody treatment, indicating a potential effect of ADCC on outcome for certain indications. Furthermore, the use of therapeutic antibodies after allogeneic haematopoietic stem cell transplantation is an interesting option. Studying the role of the FcγRIIIa-V158F polymorphism and the influence of KIR-receptor-ligand incompatibility on ADCC in this approach may contribute to future transplantation strategies. Despite the success of approved second-generation antibodies in the treatment of several malignancies, efforts are made to further augment ADCC in vivo by antibody engineering. Here, we review currently used therapeutic antibodies for which ADCC has been suggested as effector function.